Teaching Early Years Children during COVID-19 through Digital Technologies - Iqra Asim, Muhammad Shahid Farooq (JECCE, 2023)
COVID 19 has transformed the modes of formal schooling for early childhood education from physical face to face formations to virtual interactive arrangements. This sudden outbreak created uncertainty as well as unknown fear among the masses. This grave situation and unexpected obligatory closure of early childhood schools has deprived many children to attend schools. This qualitative study was planned to explore the effect of modern technologies in engaging early learners during this period. Twenty early childhood education teachers and head teachers of public and private schools of a metropolitan city of Pakistan were interviewed. The results revealed that the education authorities accepted this situation as a challenge for engaging young children at their homes through latest technologies and software applications. It helped children to come out from the psychological melancholy and panic of the pandemic during the lockdowns. Parents and teachers faced many problems for provision of digital equipments and access to internet. They also faced quandary of not being well versed with the use of latest gadgets, software and social media for the purpose of teaching early years’ children. The practitioners are supposed to work for using such technologies on regular basis by adopting the blended learning approach at early childhood education level.